2014
DOI: 10.1002/asi.23079
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rationale awareness in online ideation crowdsourcing tasks

Abstract: Prior studies have shown that articulating and sharing rationales in traditional small-group activities contribute to the maintenance of common ground, members' knowledge awareness, and contribution awareness. It is likely that the importance of articulating and sharing rationales will be increasingly acknowledged in online crowdsourcing because in such a context, large-scale participation is expected with participants often not knowing each other and being flexible about their participation status (e.g., part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Yet, unlike their organizational counterparts, we know much less about what facilitates better retention and performance in crowds (Qin, Salter‐Townshend, & Cunningham, ). As a result, our knowledge of what leads to effective crowd work has not kept pace with the deployment of crowds in our global economy (Ransbotham & Kane, ; Xiao, ). As crowds become increasingly vital to how work gets done, there is a need to better comprehend what conditions facilitate better retention and performance (Arazy, Yeo, & Nov, ).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, unlike their organizational counterparts, we know much less about what facilitates better retention and performance in crowds (Qin, Salter‐Townshend, & Cunningham, ). As a result, our knowledge of what leads to effective crowd work has not kept pace with the deployment of crowds in our global economy (Ransbotham & Kane, ; Xiao, ). As crowds become increasingly vital to how work gets done, there is a need to better comprehend what conditions facilitate better retention and performance (Arazy, Yeo, & Nov, ).…”
Section: Introductionmentioning
confidence: 99%
“…). For instance, output quality on a creative task improves when workers are informed of other contributors’ efforts and their rationales (Xiao ).…”
Section: Distributed Processingmentioning
confidence: 99%
“…Crowdsourcing complex or creative products may require active promotion of collective learning and tailored feedback (e.g., Cullina et al 2015). For instance, output quality on a creative task improves when workers are informed of other contributors' efforts and their rationales (Xiao 2014).…”
Section: Distributed Processingmentioning
confidence: 99%
“…To examine this, Xiao proposed the concept of rationale awareness , that is, the awareness of the group members’ rationales related to the tasks (Xiao, ). The related studies suggested that the individual's rationale awareness has helped one to be better aware of the other group members’ domain expertise and intellectual contributions in idea generation activities in both small group setting (Xiao, ) and crowdsourcing situations (Xiao, ). Xiao further found that members developed practices switching between the idea space and the rationale space and there was a convergence in members’ linguistic styles in their rationales (Xiao & Carroll, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the small group study, participants complained that knowing the others’ rationales made it challenging for them to think of other ideas (Xiao, ). In the online crowdsourcing study, the rationale awareness did not improve the best quality of the generated ideas (Xiao, ).…”
Section: Introductionmentioning
confidence: 99%